(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This study aimed to evaluate the concomitant use of diuretics, angiotensin-converting-enzyme inhibitors/ angiotensin receptor blocker (ACEIs/ARBs) and non-steroidal anti-inflammatory drugs, frequently termed as â€œTriple Whammy,â€ prescribed among out-patients. It also aimed to determine the impact of this combination on patientsâ€™ renal function. Methodology: A retrospective and observational study was conducted in a hospital located in the state of Selangor, Malaysia. Patients who were receiving two or more of triple whammy agents were reviewed and analyzed. The associations between the prescriptions and patientsâ€™ demographics and comorbidities were tested using the Chi-square test. On the other hand, a paired sample t-test was used to determine the impact of prescriptions on renal function with a consideration of statistical significance when P < 0.05. Results: Out of 412 prescriptions (60.2% male) were included in this study, 407 prescriptions were containing two of the mentioned medication with only 5 prescriptions for triple whammy. The majority of prescriptions had (64.1%) ACEIs/ARBs and diuretics, and it was mainly prescribed to hypertensive patients (98.5%) aged less than 65 years old (38.3%). Furthermore, males were more likely to receive this combination of ACEIs/ARB and diuretics than females (P < 0.001) due to the fact that the male gender is considered as a risk factor for cardiovascular conditions that require ACEIs/ARBs + diuretics. In addition, there was a statistically significant decrease in CrCl after these risky combinations were initiated. Conclusion: The prescribing trend of triple whammy during the period of data collection was low compared to prescriptions of two risky combinations. This is indeed a good predictor of safe prescribing of drugs among physicians, as concomitant use of these three medications may impair renal functions.